KEMAMPUAN MOBILITAS GERAK ANAK USIA DINI 4 SAMPAI 5 TAHUN MELALUI GERAKAN-GERAKAN SENAM - Yoga Esra Sinaga; Rachmi Marsheilla Aguss (Journal of Arts and Education, 2021)
Gymnastic movements can support the physical development of the child such as strength and endurance of muscles. This study aims to find out how teachers' efforts in developing the mobility of early childhood movements 4-5 years through gymnastic movements at tk Negeri Panjang Bandar Lampung. This research is a study involving 2 teachers in class A, the results showed that the efforts of teachers in developing the mobility of children's movement through gymnastic movements in group A as follows: (1) Teachers prepare music and determine the gymnastics used (2) Teachers give guidance to children about gymnastics (3) Teachers arrange the division of rows of children (4) Teachers give examples of gymnastics movements (5) Gymnastics Begins. The teacher's process in developing children's mobility through gymnastic movements has been carried out well. Educators do not have to emphasize the level of success that children do but rather have to look at each child's abilities, because the ability of the child is different.